2013
DOI: 10.1016/j.jtcvs.2012.09.091
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial lesions do not improve the efficacy of a complete left atrial lesion set in the surgical treatment of atrial fibrillation, but they do increase procedural morbidity

Abstract: Objective Some have suggested the superiority of biatrial versus left atrial lesions. We sought to analyze our experience. Methods We retrospectively reviewed 305 consecutive patients from 2007 to 2011. Rhythm success was defined as freedom from atrial fibrillation (AF) or flutter determined by 12-lead electrocardiograms at 3-month intervals. Lesions sets were pulmonary vein isolation (PVI), left-extended (PVI + mitral valve annulus [MV] lesion ± left atrial appendage lesion [LAA]) or biatrial-extended (righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 24 publications
(28 reference statements)
5
54
0
8
Order By: Relevance
“…These authors found similar differences between lesion sets 45 when operations were performed in patients undergoing concomitant mitral valve surgery. An ongoing NIH sponsored clinical trial comparing biatrial ablation, extended LA ablation and no treatment in AF patients undergoing mitral valve surgery should help clarify this issue (ClinicalTrials.gov identifier: NCT00903370).…”
Section: Extended La Lesion Setsmentioning
confidence: 64%
See 1 more Smart Citation
“…These authors found similar differences between lesion sets 45 when operations were performed in patients undergoing concomitant mitral valve surgery. An ongoing NIH sponsored clinical trial comparing biatrial ablation, extended LA ablation and no treatment in AF patients undergoing mitral valve surgery should help clarify this issue (ClinicalTrials.gov identifier: NCT00903370).…”
Section: Extended La Lesion Setsmentioning
confidence: 64%
“…45 Unfortunately, because of uncorrected differences in baseline patient characteristics between groups, the heterogeneity of lesion sets and ablation technology, the performance of multiple subanalyses, rhythm follow-up with only electrocardiography and failure to report freedom from AADs, these data are extremely difficult to interpret. Moreover, the significant differences between groups suggest that there was a fairly prominent uncontrolled selection bias in what lesion sets were chosen for different patients.…”
Section: Extended La Lesion Setsmentioning
confidence: 99%
“…However, it remains unclear whether biatrial ablation is more effective and safer than limited left or right atrial ablation [8-10, 12, 13]. Soni lK et al [12] concluded that the addition of a right atrial lesion to an extended left atrial lesion set did not improve efficacy, but it did increase the rate of pacemaker placement for sinus dysfunction. conversely, Kim JB et al [13] considered that biatrial ablation was more effective for the restoration and maintenance of sinus rhythm without increasing the risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Недавние исследова-ния, включая два рандомизированных [1,5], вы-явили сопоставимую эффективность как лево-предсердной (ЛП), так и биатриальной (БА) аб-лации [6,7], в то же время другие исследования, включая два метаанализа, показали, что БА-аб-лация способствует более длительной свободе от возврата ФП [4,8,9]. Основным ограничением для выполнения БА-аблации является более вы-сокий риск имплантации искусственного води-теля ритма (электрокардиостимулятора -ЭКС) [6,8,10]. Некоторые авторы утверждают, что БА-аблацию разумно выполнять у пациентов с пер-систирующей или длительно персистирующей ФП [4,11,12].…”
Section: Introductionunclassified
“…Soni et al показано, что БА-схема фрагментации была ассоциирована с бо-лее высокой частотой случаев имплантации ЭКС (7,5% против 16,5%, р = 0,02), в том числе по причине дисфункции синусного узла (3,7% против 12,1%, р < 0,01), независимо от других операционных факторов [6]. В недавнем мета-анализе частота имплантации ЭКС в ЛП-и БА-группах составила 5,4 и 7,0% соответственно (р = 0,008) [8].…”
unclassified